Lectura Recreativa para mejorar la Comprensión Lectora en Lengua y Literatura, Quinto Grado “B”, Escuela “Rosa Josefina Burneo de Burneo”, Loja, 2023-2024 - Torres González, María Alexandra (2024)
Reading comprehension is fundamental in the academic formation of students, especially in the Language and Literature Fifth Grade. This study seeks to determine the importance of recreational reading to improve reading comprehension in the Fifth Grade "B" of the "Rosa Josefina Burneo de Burneo" School. The specific objectives of the research are: to diagnose the impact of reading comprehension based on recreational reading, to propose an alternative proposal for the improvement of reading comprehension, and to evaluate reading comprehension based on recreational reading. The impact of reading comprehension based on recreational reading was diagnosed through an observation form and a survey applied to students. Then, an alternative proposal with creative activities for the improvement of reading comprehension was raised and its effectiveness was evaluated. The methodology included a mixed approach, exploratory research, descriptive and a quasi-experimental design. Techniques such as direct observation, student survey and teacher interview were applied to obtain a holistic view of the impact of recreational reading on reading comprehension. The results showed that recreational reading significantly improved students' reading comprehension, but rather also increased their interest and motivation towards reading, contributing to their academic and personal development, noting that the implementation of recreational reading activities is an effective strategy to strengthen reading skills. Therefore, recreational reading is fundamental to improve reading comprehension and motivate students in the learning process.